ANALISIS KETERKAITAN PRODUKTIVITAS PERTANIAN DAN IMPOR BERAS DI INDONESIA - Headhi Berlina Siringo; Murni Daulay (Departemen Ekonomi Pembangunan USU, 2014)
This research titled “Analysis Causality of Agricultural Productivity and Import of Rice in Indonesia”. The purpose of this research is to know relationship between agricultural productivity and imported rice in Indonesia. The research uses secondary data from 1986 until 2012. The method of analisys are Unit Root Test, Ordinary Least Square, and Grager Causality. This data is processed by using the program eviews 7.1. The results of the research show that there is a reciprocal relationship (causality) between agricultural productivity and imported rice in Indonesia, based on a simple regression test results indicate that there is a negative relationship between agricultural productivity and imported rice, and there is a negative relationship between imports of rice and agricultural productivity in Indonesia.Key words: Agricultural Productivity, imported rice, The Granger Causality Test, and Ordinary Least Square.